High glucose‐induced oxidative stress increases IL‐8 production in human gingival epithelial cells. (29th June 2016) - Kashiwagi, Y; Takedachi, M; Mori, K; Kubota, M; Yamada, S; Kitamura, M; Murakami, S
Abstract : Objective: Diabetes is often associated with increased prevalence and severity of periodontal disease. We hypothesized that gingival epithelial cells modify periodontal disease progression and predicted that hyperglycemia would activate an inflammatory response in human gingival epithelial cells (HGECs). Materials and Methods: We tested our hypothesis in immortalized HGECs (epi 4 cells) isolated from periodontal tissue and transfected with the simian virus 40 T antigen. The epi 4 cells were cultured in high (25 mM, HG) and normal (6 mM, NG) glucose conditions. Results: The epi 4 cells showed increased interleukin‐8 (IL‐8) protein secretion and mRNA expression when cultured in HG, compared with in NG. These effects were not associated with increased cell proliferation and were not observed in a hyperosmolar control group (normal glucose with 19 mM mannitol). Increased IL‐8 secretion in HG was inhibited by pretreatment with an antioxidant, N‐acetylcysteine, or a protein kinase C inhibitor, Ro31‐8220. Hyperglycemia did not affect IL‐8 secretion by gingival fibroblasts or periodontal ligament cells. In epi 4 cells, hyperglycemia also induced expression of toll‐like receptor 2 (TLR2) but not TLR4. Conclusion: These findings suggest a potential participation of epithelial cells in periodontal disease during diabetes by evoking an excessive host inflammatory response.